Canonical Quantization of Higher-Order Lagrangians - Khaled I. Nawafleh (Journal of Applied Mathematics)
After reducing a system of higher-order regular Lagrangian into first-order singular Lagrangian using constrained auxiliary description, the Hamilton-Jacobi function is constructed. Besides, the quantization of the system is investigated using the canonical path integral approximation.